Implementation of Corporate Social Responsibility and Communication (CSR) at PT. Pertani (Persero) - Ririn Frebianti; Nurita Andriani; Muh. Syarif (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Implementation of Corporate Social Responsibility and Communication (CSR) at PT. Farmers (Persero). This research is a qualitative descriptive research. This type of research is not to elaborate explanations, control communication symptoms or make predictions, but rather to provide an overview and understanding (understanding) of how and why a symptom or reality of communication occurs. The data collection technique used in this study was in-depth interviews. This type of interview contains questions that are "open ended", leads to a depth of information, and is conducted in an unstructured way. Based on the results of research conducted by researchers at PT. Pertani (Pesero), implementing the CSR program of PT. Pertani (Persero) carries out selective processes such as community data, proposals, evaluations, according to criteria, rejected, principle permits, implementation processes, implementation reports, evaluations and CSR profiles so that the program will be implemented effectively and the quality of the benefits is good for the impact of the program itself , In the context of community empowerment, the communication strategy developed by the company with the beneficiary communities greatly influences the success of the CSR program. In implementing the CSR program, communication activities are important to do.